Effect of low-intensity pulsed ultrasound on mast cell degranulation and fibroblast expression on type 2 diabetes mellitus rats wound healing process - Intan Maharani; Cahya Yustisia Hasan; Bambang Dwirahardjo; Tri Wahyu Pangestiningsih (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Impaired wound healing is one of the Diabetes mellitus complications. Low-intensity Pulsed Ultrasound (LIPUS) therapy may accelerate the impaired wound healing. The use of LIPUS therapy in the early inflammatory phase can induce mast cell degranulation, and in the proliferative phase it can increase collagen synthesis by fibroblasts. The purpose of this study was to determine the effects of LIPUS therapy on mast cell degranulation and fibroblastexpression in the healing process of punch biopsy wound in rats with type 2 diabetes mellitus. Twenty-four Sprague dawley (n=24) were designed into type 2 diabetes mellitus by injecting Nicotinamide and Streptozotocin, then divided into six groups: diabetes mellitus without LIPUS (DM3, DM7, DM14) and diabetes mellitus with LIPUS (DML3, DML7, DML14), 4 each, and punch biopsy wounds were made on the dorsal skin. The DML group received LIPUS therapy in the wound area (frequency 3 MHz, intensity 0.5 W/cm2, duty cycle 20%, duration 3 minutes every day for 3 days (DML3), 7 days (DML7), and 14 days (DML14). The wounded tissue area was stained with toluidine blue to observe mast cell degranulation and immunohistochemical type HSP-47 to observe fibroblast expression. Two-Way ANOVA and Post Hoc LSD tests were used to determine the differences in mast cell degranulation and fibroblast expression. The results showed that mast cell degranulation and fibroblast expression in the DML group were higher than in the DM group (table 1). Pearson test showed a correlation between mast cell degranulation and fibroblast expression (p=0.00; r= 0.839). LIPUS therapy increases mast cell degranulation and fibroblast expression in type 2 diabetes mellitus rat model. The higher the mast cell degranulation, the higher fibroblast expressions.